Sociology and Anthropology Approaches in Islamic Studies - Yondrizal, Yondrizal; Julhadi (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2025)
Sociology and anthropology approaches offer unique perspectives in understanding Islam as a social and cultural phenomenon. Both allow a deeper exploration of religious dynamics, people's behavior, and Islam's interaction with society. This approach not only sees Islam as a normative teaching based on sacred texts, but also as a social system that continues to develop. This research uses a qualitative method with literature study as a data collection technique. In the context of Islamic education, the sociology approach helps to understand how social structure, environment and policies affect religious learning, while anthropology highlights the role of tradition and local wisdom in the educational process. Islamic education aims not only to transfer religious knowledge, but also to shape character, internalize social norms and adapt to cultural changes. This approach makes Islamic education more contextual, relevant and inclusive, enabling learners to understand and apply Islamic teachings in social life. In conclusion, the application of sociology and anthropology in Islamic education can enrich insights into the relationship between religion and social reality, bridge tradition and innovation, and encourage inclusiveness in religious practice in modern society.